Voluntary frontier settlement and independent agency within China - Xiaopeng Ren; Yiwei Zhang (Acta Psychologica)
Voluntary frontier settlement has led to independent agency in Western and a few non-Western societies. This study suggests that Northeast China was constructed as a new region with voluntary frontier settlers during 1860–1920, and examined whether voluntary frontier settlement predicted individualistic differences by comparing inhabitants from Northeast China (N = 479) to those in contrast region where their ancestors originated (N = 520) with multiple cultural tasks. Results showed that inhabitants of Northeast China were higher in self-reported individualism and happiness related to more socially disengaging emotions, and fewer in-group favoritism and less holistic thought compared to the inhabitants of North China. Overall, this suggests that voluntary frontier settlement played an important role in the individualistic differences between Northeast China and North China.